(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to a comparative criminal legal analysis of the provisions of the Additional Protocol to the Convention on Cybercrime, which concerns the criminalization of racist and xenophobic acts committed through computer systems, and the Criminal Code of Ukraine. As a result of the detection of gaps in the criminal law regulation, a number of changes and additions to Articles 67, 161, 300 of the Criminal Code of Ukraine were proposed. In addition, on the basis of the primary criminalization of crimes against humanity, it is proposed to implement the secondary criminalization of public denial, significant minimization, approval or justification of genocide or crimes against humanity, the commission of which is established by the verdicts of international judicial bodies, the courts of Ukraine or recognized by the decision of the Verkhovna Rada of Ukraine, as well as the production of material, which denies, significantly minimizes, condones, or condones acts that constitute genocide or crimes against humanity for the purpose of distributing, disseminating, or otherwise providing public access through computer systems to such materials.